Case Report: Exploring the spectrum of A20 haploinsufficiency in children - Jayaraman, Sahana; Balmuri, Nayimisha (Frontiers in Pediatrics, 2025)
Haploinsufficiency of A20 (HA20), caused by TNFAIP3 mutations, is a rare autoinflammatory syndrome characterized by highly variable, multisystem manifestations that often delay recognition and definitive care. The A20 protein restrains NF-κB–mediated pro-inflammatory signaling; therefore, loss-of-function variants unleash widespread inflammation that can involve virtually any organ. Fewer than 200 cases have been reported worldwide; thus, clinicians have limited phenotype-specific guidance. We describe four unrelated patients evaluated at a single tertiary center, each carrying a distinct TNFAIP3 mutation and exhibiting a unique clinical picture ranging from mucocutaneous ulcerations and Behçet-like vasculitis to lupus-like autoimmunity and periodic fever with arthritis. Tailored therapies were selected to match the dominant inflammatory pathway and produced durable clinical remission in all cases. By linking genotype, phenotype, and therapeutic response, this case series broadens the clinical spectrum of HA20 and offers practical, phenotype-driven strategies to improve screening, diagnosis, and individualized management.